Base excision DNA repair defect in thioredoxin-1 (Trx1)-deficient cells - Hye Lim Kim (2018)
Thioredoxin-1 (Trx1) is an antioxidant enzyme with a protective role in the removal of oxidative stress. We investigated the mechanism by which the redox modulator Trx1 affects base excision repair (BER) activity to understand the protective role of Trx1. We constructed a Trx1 knockdown system to demonstrate the specific mechanism of Trx1. DNA damage in terms of relative intensity of the DNA tail and γ-H2AX foci was markedly higher in the Trx1 shRNA cells compared with that in the wild type cells, leading to increased cellular susceptibility to a sublethal dose of BER-inducible toxicant, nitrosomethylurea (NMU). In addition, we observed a modulatory role of Trx1 in the BER pathway via the p53 downstream gene, growth arrest, and DNA-damage-inducible protein 45 α (Gadd45a). The protein level and function of p53, a Trx1 downstream gene, coincidently decreased in the Trx1 shRNA cells. Furthermore, Trx1 shRNA cells showed decreased Gadd45a expression and interaction of Gadd45a with apurinic/apyrimidinic endonuclease 1 (APE1) as well as APE1 activity. In conclusion, Trx1 might cooperate in the control of APE1 function by modulating the p53-mediated BER via the protein-protein interaction between Gadd45a and APE1, providing insight into the novel role of redox factor Trx1 in modulation of BER. © 2013 Elsevier B.V.